Experimental hut evaluation of a novel long-lasting non-pyrethroid durable wall lining for control of pyrethroid-resistant Anopheles gambiae and Anopheles funestus in Tanzania. (December 2017) - Malima, Robert; Emidi, Basiliana; Messenger, Louisa; Oxborough, Richard; Batengana, Bernard; Sudi, Wema; Weston, Sophie; Mtove, George; Mugasa, Joseph; Mosha, Franklin; Rowland, Mark; Kisinza, William
Abstract Background A novel, insecticide-treated, durable wall lining (ITWL), which mimics indoor residual spraying (IRS), has been developed to provide prolonged vector control when fixed to the inner walls of houses. PermaNet® ITWL is a polypropylene material containing non-pyrethroids (abamectin and fenpyroximate) which migrate gradually to the surface. Methods An experimental hut trial was conducted in an area of pyrethroid-resistantAnopheles gambiae s.l. andAnopheles funestus s.s. to compare the efficacy of non-pyrethroid ITWL, long-lasting insecticidal nets (LLIN) (Interceptor® ), pyrethroid ITWL (ZeroVector® ), and non-pyrethroid ITWL + LLIN. Results The non-pyrethroid ITWL produced relatively low levels of mortality, between 40–50% forAn. funestus andAn. gambiae, across all treatments. AgainstAn. funestus, the non-pyrethroid ITWL when used without LLIN produced 47% mortality but this level of mortality was not significantly different to that of the LLIN alone (29%, P = 0.306) or ITWL + LLIN (35%, P = 0.385). Mortality levels forAn. gambiae were similar toAn. funestus with non-pyrethroid ITWL, producing 43% mortality compared with 26% for the LLIN. Exiting rates from ITWL huts were similar to the control and highest when the LLIN was present. An attempt to restrict mosquito access by covering the eave gap with ITWL (one eave openvs four open) had no effect on numbers entering. The LLIN provided personal protection when added to the ITWL with only 30% blood-fed compared with 69 and 56% (P = 0.001) for ITWL alone. Cone bioassays on ITWL with 30 min exposure after the trial produced mortality of >90% using fieldAn. gambiae. Conclusions Despite high mortality in bioassays, the hut trial produced only limited mortality which was attributed to pyrethroid resistance against the pyrethroid ITWL and low efficacy in the non-pyrethroid ITWL. Hut ceilings were left uncovered and may have served as a potential untreated refuge. By analogy to IRS campaigns, which also do not routinely treat ceilings, high community coverage with ITWL may still reduce malaria transmission. Restriction of eave gaps by 75% proved an inadequate barrier to mosquito entry. The findings represent the first 2 months after installation and do not necessarily predict long-term efficacy.